PENGARUH SUHU MEDIA PEMBEKU TERHADAP EFISIENSI EKSERGI DAN LAJU PEMBEKUAN - D. Mustofa K.; A. H. Tambunan; S. T. Soekarto; Radite Praeko A. S (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT The concept of exergy is defined as the maximum theoretical work that would be delivered by a system as it comes into equilibrium with the environment. This method is used to analyze the freezing process. Objective of the research is study of effect medium temperature toward exergy efficiency and freezing rate.The research indicated that lower medium temperature of freezer resulted in a higher freezing rate but with lower exergy officiency. In case of sliced beef meat, freezing rate of 3 cm/h can be obtained with temperature stage of Tma = -3 oC, Tmf = -15 and Tmb = -21 oC, with exergy efficiency 58 %.Diterima: 12 Januari 2007, Disetujui: 20 Mei 2007